Evaluation of the Forsvall biopsy needle in an ex vivo model of transrectal prostate biopsy – a novel needle design with the objective to reduce the risk of post-biopsy infection. (4th May 2021) - Forsvall, Andreas; Fisher, Jane; Cardoso, José Francisco Pereira; Wagenius, Magnus; Tverring, Jonas; Nilson, Bo; Dahlin, Andreas; Bratt, Ola; Linder, Adam; Mohanty, Tirthankar
Abstract: Background: Transrectal prostate biopsy (TRbx) transfers colonic bacteria into prostatic tissue, potentially causing infectious complications, including sepsis. Our objective was to determine whether biopsy needle shape, surface properties and sampling mechanism affect the number of bacteria transferred through the colon wall, and evaluate a novel needle with improved properties. Methods: The standard Tru-Cut biopsy needle used today was evaluated for mechanisms of bacterial transfer in a pilot study. A novel Tru-Cut needle (Forsvall needle prototype) was developed. TRbx was simulated using human colons ex-vivo. Four subtypes of the prototype needle were compared with a standard Tru-Cut needle (BARD 18 G). Prototype and standard needles were used to puncture 4 different colon specimens in 10 randomized sites per colon. Needles were submerged into culture media to capture translocated bacteria. The media was cultured on blood agar and then the total amount of transferred bacteria was calculated for each needle. The primary outcome measure was the percent reduction of bacteria translocated by the prototype needles relative to the standard needle. Secondary outcome measures were the effects of tip design and coating on the percent reduction of translocated bacteria. Results: Prototype needles reduced the number of translocated bacteria by, on average, 96.0% (95% confidence interval 93.0-97.7%; p  < 0.001) relative to the standard needle. This percent reduction was not significantly affected by prototype needle tip style or surface coating. Conclusions: The Forsvall needle significantly reduces colonic bacterial translocation, suggesting that it could reduce infectious complications in prostate biopsy. A clinical trial has been initiated.